2002
DOI: 10.1063/1.1502645
|View full text |Cite
|
Sign up to set email alerts
|

Computer simulations of the dynamics of doubly occupied N2 clathrate hydrates

Abstract: We have studied the dynamical properties of doubly and singly occupied structure II N2 clathrate hydrates by performing a series of classical molecular dynamics calculations. The intermolecular vibrational density of states of the guest molecules show the most explicit changes when going from single to double occupancies. Instead of the narrow peak for single occupancy (at 20 cm−1), a broad range of frequencies occurs between 0 and 200 cm−1 with four modes, which have been assigned to the possible vibrations i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 37 publications
0
19
0
Order By: Relevance
“…17 This choice of force field for the clathrate and guests gives good estimates for the lattice vectors and other experimental data available in the equilibrated clathrates. 22,23 Isotropic constant pressure/temperature NpT molecular dynamics simulations on periodic simulation cells were performed using the DL_POLY software program version 2. 16.…”
Section: Molecular Dynamics Methodsmentioning
confidence: 99%
“…17 This choice of force field for the clathrate and guests gives good estimates for the lattice vectors and other experimental data available in the equilibrated clathrates. 22,23 Isotropic constant pressure/temperature NpT molecular dynamics simulations on periodic simulation cells were performed using the DL_POLY software program version 2. 16.…”
Section: Molecular Dynamics Methodsmentioning
confidence: 99%
“…[14][15][16] Only few simulations results for a N 2 clathrate can be found in the literature. [17][18][19][20][21][22] Horikawa et al, and later van Klaveren et al, have studied the dynamical behavior of encaged N 2 molecules using molecular dynamics (MD). 17,21 van Klaveren et al have shown also that a N 2 hydrate with sII at high pressure remains mechanically stable even for the case of a full double occupancy of the large cages.…”
Section: Introductionmentioning
confidence: 99%
“…5 These results support the double occupation determined by the above neutron diffrac-tion measurements. Klaveren et al also calculated the vibrational frequencies for sII nitrogen hydrate, 6,7 in which they showed three N-N stretching peak frequencies for the single occupied S cages, the double occupied L cages, and the single occupied L cages. 6 Although a number of Raman experiments for the N-N stretching vibrations in natural or synthetic air hydrates have been performed, [8][9][10][11][12][13][14][15] there is no evidence for the double occupancy.…”
Section: Introductionmentioning
confidence: 99%